Direct volumetric measurement of crystallographic texture using acoustic waves. (15th October 2018) - Lan, Bo; Ben Britton, T.; Jun, Tea-Sung; Gan, Weimin; Hofmann, Michael; Dunne, Fionn P.E.; Lowe, Michael J.S.
Abstract: Crystallographic texture in polycrystalline materials is often developed as preferred orientation distribution of grains during thermo-mechanical processes. Texture dominates many macroscopic physical properties and reflects the histories of structural evolution, hence its measurement and control are vital for performance optimisation and deformation history interogation in engineering and geological materials. However, exploitations of texture are hampered by state-of-the-art characterisation techniques, none of which can routinely deliver the desirable non-destructive, volumetric measurements, especially at larger lengthscales. Here we report a direct and general methodology retrieving important lower-truncation-order texture and phase information from acoustic (compressional elastic) wave speed measurements in different directions through the material volume (avoiding the need for forward modelling). We demonstrate its deployment with ultrasound in the laboratory, where the results from seven representative samples are successfully validated against measurements performed using neutron diffraction. The acoustic method we have developed includes both fundamental wave propagation and texture inversion theories which are free from diffraction limits, they are arbitrarily scalable in dimension, and can be rapidly deployed to measure the texture of large objects. This opens up volumetric texture characterisation capabilities in the areas of material science and beyond, for both scientific and industrial applications. Graphical abstract: Powered by a general theoretical platform that links the polycrystal texture with acoustic wave speeds via a simple convolution relationship, rapid non-destructive measurements of volumetric texture are achieved using the conventional water-bath ultrasonic system. The results of seven representative hexagonal and cubic samples are successfully validated against the well-established neutron diffraction technique. Image 1